PREPARATION OF LYMPHOCYTE CULTURE CELL FROM PERIPHERIAL BLOOD OF NASOPHARYNGEAL CARCINOMA PATIENTS - Aris Haryanto; Sofia Mubarika; Nastiti Wijayanti (Jurnal Sain Veteriner, 2000)
Lymphocyte is leukocyte component that difficult to culture in vitro. Several viruses need lymphocytes as host cell in order to proliferate and growth in this media such as Epstein-Barr virus (EBV). This virus was associated with malignant disease like nasopharyngeal carcinoma (NPC). The objectives of this research are to develop and to prepare lymphocyte cell culture as material source of DNA for molecular analysis of virus. Peripheral blood was collected from NPC patients which is histopatologically and serologically positive of EBV. Lymphocytes were separated from the other blood components using ficcol-histopaque. Lymphocytes were diluted using RPMt medium then they were cultivated into 96 microwell plate with concentration of 106 cell/ml. The medium consist of 10% FBS, RPMI, Penstrep and FK 506. Culture of lymphocytes were incubated in 5% CO2 at 37°C. The lymphocyte cultures developed and grew confluendy during the first week. Only B cells whith EBV would be well establish. After 50 cell generations, lymphocytes were transformed and immortalized to be lymphoblastoid cell fine (LCL).